The effect of using the learning cycle model on achievement and the development of creative thinking among middle school students in the Holy Quran and Islamic education - dr.Alaa Hussein Faraj (Journal of College of Education, 2024)
The aim of this research is to find out The effect of using the learning cycle model on achieving and developing creative thinking Among middle school students in the Holy Quran and Islamic education The research sample consisted of (64) first-year intermediate students Then they were randomly distributed into two groups. The first experimental group includes (31) students and was taught using the learning cycle model. The second control group included (33) students who studied using the traditional method The researcher prepared two tests, one of which was an achievement test and the other a creative thinking test The research results showed that there were statistically significant differences between the study members due to the method used in achievement and creative thinking. And in favor of students who studied using the learning cycle compared to students who studied in the traditional method